Epidemiologia do acidente por serpentes peçonhentas: estudo de casos atendidos em 1988 Epidemiology of poisonons snake-bites: a study of cases assisted in 1988 - Lindioneza Adriano Ribeiro; Miguel Tanús Jorge; Lygia Bush Iversson (Universidade de São Paulo, 1995)
Foram avaliados aspectos epidemiológicos de acidentes por serpentes peçonhentas no Estado de São Paulo, Brasil, com base em prontuários de 322 pacientes e em entrevistas feitas com 209 deles e/ou seus acompanhantes. Os acidentes ocorreram principalmente com pessoas de 10 a 20 anos de idade, do sexo masculino, nos meses de outubro a abril e no período diurno. As regiões anatômicas mais freqüentemente picadas foram os pés, as mãos e as pernas. Bothrops, Crotalus e Micrurus foram responsáveis por, respectivamente, 95,0%, 4,4% e 0,6% dos casos. Não ocorreram óbitos, mas 2,2% dos pacientes apresentaram seqüelas. Dentre os 209 entrevistados, a ocupação de lavrador foi a mais freqüentemente relacionada ao acidente que, em aproximadamente 60% das vezes, ocorreu durante o trabalho. O total de 160 pacientes (76,6%) submeteram-se a alguma forma de tratamento antes de chegarem a um serviço de saúde: foram mais comuns o uso de torniquete (50,2%), a expressão local na tentativa de retirar parte do veneno (33,5%), a colocação das mais diversas substâncias sobre o local da picada (36,8%) e a ingestão de outras (12,9%); pouco mais de um quarto dos pacientes submeteram-se a alguma forma de tratamento médico antes de chegar ao HVB sendo mais comum a antissepsia (8,2%), a administração do antiveneno (6,2%), de anti-histamínicos (5,7%) e de analgésicos (5,3%). The attendance given to patients by ta specialized Hospital, in S.Paulo, Brazil, during 1988 is studied. The study is based on the medical records of 322 patients and on questionnaires filled out by author during interviews with 209 patients or their companions. The 322 snake-bites occurred mainly between October and April, in the diurnal period, mainly in the afternoon. Most of patients were adult males, mainly between 10 and 20 years of age. The parts of the body most fequently affected were the feet, hands and legs. The snakes of the genera Bothrops, Crotalus and Micrurus were responsible, respectively, for 306 (95.0%) 14 (4.4%) and 2 (0.6%) of the accidents under study. Among the 160 snakes that were classified at the Herpetological Section of the IB, 152 were Bothrops; 142 B. jararaca, mostly young reptiles, and 8 were of the genus Crotalus. Of the patients, 90.4% recovered completely, 2.2% presented sequelae, 7.5% were transferred and thus it was impossible to follow them up. Of the 209 persons interviewed, the occupational group most prone to snake bites was agricultural workers, followed by studentes; nearly 60% of the accidents ocurred during work; most of the patients had their inferior extremities unprotected at the moment of the bite. On hundred and sixty patients (76.6%) submitted to some from of treatment before coming to the HVB-IB, the more common being the use of a tourniquet (50.2%), local squeezing in an attemp to remove part of the venom (33.5), application of substances on the site of the snake bite (36.8%) and the ingestión of others (12.9%). Slightly over a quarter of the patients underwent some kind of medical treatment before coming to the HVB-IB, the most common being antissepsis (8.2%), administration of antivenom (6.2%), antihistamines (5.7%) and analgesics (5.3%). The snake was seen before it struch by 187 (89.5%) of the 209 persons interviewed and in most cases it adopted the strike posture just before the first bite.